2010
DOI: 10.1007/s00535-010-0268-7
|View full text |Cite
|
Sign up to set email alerts
|

Can pancreatic duct stenting prevent post-ERCP pancreatitis in patients who undergo pancreatic duct guidewire placement for achieving selective biliary cannulation? A prospective randomized controlled trial

Abstract: Pancreatic duct stenting after P-GW for achieving selective biliary cannulation is recommended to reduce the incidence of post-ERCP pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
111
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 15 publications
1
111
1
3
Order By: Relevance
“…Although prophylactic pancreatic duct stenting can reduce the incidence of post-ERCP pancreatitis in patients at high risk (8)(9)(10)(11)(12)(13), it is impossible to completely prevent it. Therefore, endoscopists who perform ERCP should always be aware of the possible occurrence of this particular complication after the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prophylactic pancreatic duct stenting can reduce the incidence of post-ERCP pancreatitis in patients at high risk (8)(9)(10)(11)(12)(13), it is impossible to completely prevent it. Therefore, endoscopists who perform ERCP should always be aware of the possible occurrence of this particular complication after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Tarnasky et al (8) reported that pancreatic stent (5 or 7 Fr in diameter, 2 or 2.5 cm in length) placement reduced the incidence of post-ERCP pancreatitis from 26% to 7% in patients with pancreatic sphincter hypertension who had undergone biliary sphincterotomy. In a recent study by our group (13), pancreatic duct stent (5-Fr, 3-cm-long, single pigtail, no flanged) placement reduced the incidence of post-ERCP pancreatitis from 23% to 2.9% in patients who had undergone pancreatic duct guidewire placement for achieving selective biliary cannulation.…”
Section: Introductionmentioning
confidence: 99%
“…Independent risks for PEP were found to be female gender (OR: 1.84, P =0.002), age≤60 years (OR: 1.59, P =0.025), cannulation time >10 min (OR: 1.76, P =0.012), ≥1 pancreatic deep wire pass (OR: 2.77, P <0.001), and needle-knife precut (OR: 4.34, P <0.001) Interestingly, contrast injections were not found to be independently signifi cant in this study once the other factors were adjusted for. Every subsequent study to evaluate pancreatic guidewire passage as a risk factor has resulted in the same fi nding (8)(9)(10).…”
Section: Editorialmentioning
confidence: 97%
“…Best results will come from a collective approach incorporating all of the "4 Ps-patient selection, procedural variables including very careful guidewire manipulation, pancreatic stents as indicated, and pharmacologic techniques. ( 10 ) randomized 70 patients who underwent pancreatic guidewire assisted biliary cannulation to pancreatic stent ( n =35) or no stent ( n =35) and found out that the rate of PEP was signifi cantly lower in the group with pancreatic stent (2.9 vs. 23%). Th is leads to the conclusion that if deep wire passage into PD is a risk factor and PD stents can reverse that risk, then PD wire passage should either be avoided or followed by a PD stent.…”
Section: Editorialmentioning
confidence: 99%
“…Secondly, if stenting is performed at the end of the procedure, the procedure, which already has a long duration, will be extended, since it is necessary to cannulate the main pancreatic duct once again. In addition, there is a small possibility of not inserting a pancreatic stent, which is per se associated with an increase in the PEP rate [28]. A study involving 146 patients in whom pancreatic stenting was attempted after PGW-assisted cannulation reported an unsuccessful rate of 14%; the rate of pancreatitis was 4.2% in the stent group versus 29% in the group in which it was not possible to insert a stent [29].…”
Section: Discussionmentioning
confidence: 99%